Foreign Direct Investment - Growth Linkage in Sub-Saharan Africa: Is Governance a Mediating Factor? - Fagbemi, Fisayo; Bello, Kehinde Mary (International Journal of Business, Economics and Management, 2019)
In sub – Saharan Africa, weak institutions and the rising concern for improved business environment offer considerable leverage for enhancing the effectiveness of institutional framework, capital inflows, and public investment efficiency. These have put SSA in the global spotlight in recent times. Hence, the study examines the mediating effect of governance on FDI – growth nexus in 35 SSA countries between 2002 and 2017 using panel data techniques (Pooled OLS, Fixed Effects, and Panel-Corrected Standard Error’ (PCSE) estimation) and the Dynamic One – Step Difference and System GMM. Results indicate that control of corruption, political stability and regulatory quality, including governance composite index, have a positive and significant effect on economic growth, suggesting that institutions have a salutary impact on SSA economies. The findings further show that FDI inflows adversely influence growth owing to insufficient absorptive capacity that could enhance FDI effectiveness in the region. More importantly, the pervasiveness of poor governance in SSA is identified as a critical case that undermines the development of the nexus between FDI and economic growth. Thus, the study suggests that FDI – growth linkage would be enhanced by promoting a strong institutional environment that offers a good mechanism for attaining the actual FDI spillover potential through a policy framework that points the path towards cost-effective measures in SSA. Also, there should be core investment policies across African countries that would induce the private sector in consolidating government efforts and resources aimed at improving international competitiveness by diversifying the region’s economies away from a protracted commodity – based.